Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

Solve : (sqrt(6x+7) +1)=2x?------Answer: 3----i need the steps, since i cant figure out how to do it...?

thanks!

4 Answers

Relevance
  • 9 years ago
    Favorite Answer

    1. Add -1 to both sides:

    sqrt(6x+7)=2x-1

    2. Square both sides:

    6x+7 = (2x-1)^2

    3. FOIL out the right side:

    6x+7 = 4x^2-2x-2x+1

    4. Combine like terms on right:

    6x+7 = 4x^2-4x+1

    5. Subtract 6x and 7 from both sides:

    0 = 4x^2-10x-6

    6. Divide all terms by 2:

    0 = 2x^2-5x-3

    7. Factor polynomial:

    (2x+1)(x-3)=0

    8. Set each term to 0:

    either 2x+1=0 or x-3=0

    9. x = -1/2 or x = 3 (btw, -1/2 is not a full solution - it only satisfies the negative square root)

  • 9 years ago

    (i) x must satisfy the following conditions simultaneously:

    6x+7≥0 → 6x≥-7 → x≥-7/6

    Minimum of √(6x+7) is zero so 2x≥1+0 → x≥1/2

    Both conditions become one: x≥1/2

    (ii) we will rearrange and solve the equation:

    √(6x+7)+1=2x → √(6x+7)=2x-1 → (√(6x+7))²=(2x-1)² → 6x+7=4x²-4x+1

    → 4x²-10x-6=0

    x=(5±√(5²-4*(-6)))/4=(5±√(25+24))/4

    → x=(5±√49)/4=(5±7)/4=3 and -1/2

    (iii) -1/2 is in contradiction to x≥1/2 so we eliminate -1/2 and only x=3 remains.

    (iv) we should check the answer because when we square both sides of equation, some unwanted answers may appear

    √(6*3+7)+1=2*3 → √(18+7)+1=6 → √25+1=6 → 5+1=6 → 6=6

    (v) so x=3

  • 9 years ago

    sqrt(6x+7)+1=2x

    Move the 1 to the right hand side of the equation...

    sqrt(6x+7)=2x-1

    Square both sides...

    (sqrt(6x+7))^2=(2x-1)^2

    Canceling the sqrt and expanding the right hand side...

    6x+7=4x^2-4x+1

    Subtracting the left side from the right side...

    0=4x^2-10x-6

    Plugging into the quadratic formula...(a=4, b=-10, c=-6)

    x=(-b ± SQRT(b^2 - 4ac))/2a

    Simplyfying...

    x=3 or -.5...but -.5 does not satisfy the original equation, so 3 is the only solution.

  • Brenda
    Lv 7
    9 years ago

    √(6x+7) +1 =2x

    √(6x+7) =2x-1

    6x+7 = (2x-1)²

    6x+7=4x²-4x+1

    4x²-10x-6=0

    2x²-5x-3=0

    (2x+1)(x-3)=0

    x=-1/2 , x=3

    x=-1/2 isn't a valid solution as:

    √4 + 1 ≠ -1

    2≠-2

    x=3 is indeed a real solution as

    6=6

Still have questions? Get your answers by asking now.